2020
DOI: 10.22541/au.158981430.00704431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CMIP5 Climate Projections and RUSLE-Based Soil Erosion Assessment in The Central Part of Iran

Abstract: Soil erosion (SE) and climate change are closely related to environmental challenges that influence human wellbeing. However, the potential impacts of both processes in semi-arid areas are difficult to be predicted because of atmospheric variations and non-sustainable land use management. Thus, models can be employed to estimate the potential effects of different climatic scenarios on environmental and human interactions. In this research, we present a novel study where changes in soil erosion by water in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…For instance, the K factor values in dense areas such as forests and secondary forests showed low K factor values (southern, southeastern, and southwestern parts) while the agricultural and urbanized areas showed high K factor values (northern, northeastern, and northwestern parts). This was consistent with a previous study byHateffard et al (2021) that found the erodibility factor was mainly high in the agricultural area from 0.30 to 0.44 ton ha hr/ha MJ mm. The K factor values tended to reduce in regions with high elevation.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…For instance, the K factor values in dense areas such as forests and secondary forests showed low K factor values (southern, southeastern, and southwestern parts) while the agricultural and urbanized areas showed high K factor values (northern, northeastern, and northwestern parts). This was consistent with a previous study byHateffard et al (2021) that found the erodibility factor was mainly high in the agricultural area from 0.30 to 0.44 ton ha hr/ha MJ mm. The K factor values tended to reduce in regions with high elevation.…”
supporting
confidence: 93%
“…To assess the effect of future climate shifts on soil loss sensitivity, data obtained from CMIP6 by some predictions of CMIP6-SSP were applied in computing R values in the future. The used method in our work was in line with a previous study by Hateffard et al (2021) who found the predicted rainfall values would definitely cause soil erosion rate changes. The predicted soil erosion values were estimated in the study region based on the regional climate change that concerned 3 scenarios of SSPs.…”
Section: Predicted Future Soil Erosion Potential Scenariosupporting
confidence: 80%
See 1 more Smart Citation
“…The majority of current studies have been focused on erosion modeling using various automated processes and toolboxes for soil erosion estimation with the help of modern geospatial technology [28,29]. Some of the studies have also focused on soil loss potential under the context of climate change for predicting future soil loss [30,31]. However, the present study attempts to assess the rate of soil erosion by using only field data and the perceptions of local farmers regarding soil erosion and measures of soil conservation.…”
Section: Introductionmentioning
confidence: 99%